Exploring spore-forming lactic acid bacterium Heyndrickxia coagulans SANK70258 as a promising probiotic for red sea bream (Pagrus major) - Shirakashi, Shuji; Aoki, Ryuichiro; Kobayashi, Yasuhisa; Aida, Masanori; Yamada, Ryouichi; Taniguchi, Akito (Frontiers in Aquaculture, 2024)
Enhancing fish growth and bolstering immune responses to diseases are of paramount concern in fish aquaculture. The use of probiotics has emerged as a promising strategy for addressing these challenges. The aim of this study was to investigate the characteristics (salinity tolerance, starch-assimilating ability, organic acid production, β-galactosidase activity) of Heyndrickxia coagulans SANK70258 and its probiotic effects on red sea bream (Pagrus major). Our results indicate that H. coagulans SANK70258 exhibits a high salinity tolerance and thrives as a probiotic in marine environments. Moreover, its starch assimilation capability, organic acid production, and β-galactosidase activities suggest that it might play a role in enhancing the host’s immune system. Over the 63-day experimental period, supplementation with H. coagulans SANK70258 significantly increased the survival rate of red sea bream compared with that of the experimental control group (vehicle starch for the probiotic) after the final experimental day, as determined by Kaplan–Meier analysis (log-rank test, p = 0.0228). Furthermore, supplementation affected the body length and weight of fish, but it did not influence digestive enzyme activities. The goblet cell abundance in the intestinal tract of fish supplemented with H. coagulans SANK70258 was significantly higher than that in the experimental control group (Welch’s t-test, p = 0.03742). These results suggest that H. coagulans SANK70258 is a promising probiotic for enhancing marine fish aquaculture production.